Development of Land Information Maps (PIBT) Through Community Participation Using Quadcopter UAV (Case Study Desa Pojok, Kec. Tawangsari, Kab. Sukoharjo) - Widodo, Anggoro Wahyu; Budisusanto, Yanto; Cahyono, Agung Budi (Institut Teknologi Sepuluh Nopember, 2019)
The entire of land parcel in Indonesia is estimated 130million. Only about 45million land, parcels or not more than 35% of all is certified. Because of that, Government make a program called PTSL (Systematic Land Registration) to register land parcels within an area of villages. In this case, information is supporting the implementation of PTSL programme. The information formed of subject/object land parcels and with its boundary. Such information is created above the base map obtained from the process of aerial photoshoot using UAV (Unmanned Aerial Vehicle) and the collection of information through the participation of the community (Pemetaan Partisipatif). Location of the research at Pojok Village, Sukoharjo Regency. This research produced a base map formed from process orthophoto, Land Information Maps (PIBT) from Pemetaan Partisipatif and evaluating about area tolerance (KL=±0,5√L) from field measurement and result digitasi. From the results is known the information of subject/object land parcels as well as total of rice field land parcels is 615 parcels (128,598ha) and yards land parcels is 1,443 parcels (69,378ha). This information is useful for the preparation of land registry. In evaluating areas, 39 sampel accepted in area tolerance KL=±0,5√L. So, PIBT considered becomes a Land Parcels Map (PBT).